2019
DOI: 10.1186/s13104-018-4039-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the health status of childcare workers in southern Alberta, Canada

Abstract: ObjectiveThere is growing evidence that the well-being of childcare workers has important implications for the care provided to children attending childcare centers. To add to the growing body of research in this area and to lay the groundwork for further research, we report the results of a pilot study examining factors that are associated with the health status of childcare workers in southern Alberta, Canada. The factors examined include: health control, employer’s interest in the childcare worker’s wellbei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The early sexual debut was coded using the variable age at first sex among unmarried adolescents. Adolescents who experienced their first intercourse before 18 years of age were coded as 1 “early sexual debut” and 0 “otherwise” [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The early sexual debut was coded using the variable age at first sex among unmarried adolescents. Adolescents who experienced their first intercourse before 18 years of age were coded as 1 “early sexual debut” and 0 “otherwise” [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The societal norm in India is such that adolescents are expected to respect and follow traditional values and view premarital sex as undesirable and deviant from the social mores [ 4 ]. Previous studies in low-income countries found that the students who had reported early sexual debut are exposed to risky sexual behaviors such as unprotected sexual intercourse, unwanted pregnancies, unsafe abortion, and several psychosocial problems [ 21 , 22 ]. Literature also suggests that the attitudes and sexual behavior of adolescents are usually influenced by demographic and socioeconomic characteristics, especially in a country where expressed social norms often condemn premarital sex [ 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Larva, pupa, and adult mosquitoes were collected using standardized sampling methods for dengue vector surveillance ( Focks and Special Program for Research and Training in Tropical Diseases (TDR), 2003 ; Kusriastuti and Sutomo, 2005 ; WHO, 2011 ; Ritchie, 2014 ; WHO, 2016 ; MoH Indonesia, 2018 ; Harapan et al., 2019 ). In each house, larvae and pupae from different containers were put in different plastic bags.…”
Section: Methodsmentioning
confidence: 99%
“…aegypti to cause high epidemics of dengue fever in Indonesia. A total of 68,407 dengue cases (incidence: 78.85/100,000) with 493 deaths (case fatality rates (CFR): 0.72%) were reported in 2017 ( MoH Indonesia, 2018 ; Harapan et al., 2019 ). Ae.…”
Section: Introductionmentioning
confidence: 99%